THE DEVELOPMENT CONCEPT OF HALAL TOURISM IN INDONESIA IN THE NEW NORMAL - Amrin, Amrin; Yono, Yono; Zakaria, Zakaria (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2022)
The purpose of this study was to examine the concept of halal tourism development in Indonesia in the new normal era. The research uses a qualitative type with empirical and exploitation, while the data sources come from related parties such as the head of the Bima Regency office, tourism actors a,nd other parties. The secondary data comes from books, journals,and websites related to halal tourism. The techniques used in the SWOT analysis. The results show that the tourism potential towards Sharia has a great opportunity. The implementation of sharia tourism potential will run productively if there is synergy between stockholders, the tourism office and the community around the tourism locationthe concept of collaboration of various elements is indispensable in supporting the development of halal tourism.